2013
DOI: 10.1007/s13197-013-1209-2
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer modeling of convective and microwave-convective drying of oyster mushroom (Pleurotus ostreatus)

Abstract: Oyster mushroom samples were dried under selected convective, microwave-convective drying conditions in a recirculatory hot-air dryer and microwave assisted hot-air dryer (2.45 GHz, 1.5 kW) respectively. Only falling rate period and no constant rate period, was exhibited in both the drying technique. The experimental moisture loss data were fitted to selected semi-theoretical thin-layer drying equations. The mathematical models were compared according to three statistical parameters, i.e. correlation coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 21 publications
11
30
0
Order By: Relevance
“…It was also found that higher drying temperature resulted in larger heating energy leading to raising molecular water activity and raised D eff . The results of D eff value had a good agreement with the published values by other researchers (Ashtiani et al, ; Bhattacharya, Srivastav, & Mishra, ; Khoshtaghaza et al, ; Salim, Gariepy, & Raghavan, ; Wang, Li, et al, ).…”
Section: Resultssupporting
confidence: 86%
“…It was also found that higher drying temperature resulted in larger heating energy leading to raising molecular water activity and raised D eff . The results of D eff value had a good agreement with the published values by other researchers (Ashtiani et al, ; Bhattacharya, Srivastav, & Mishra, ; Khoshtaghaza et al, ; Salim, Gariepy, & Raghavan, ; Wang, Li, et al, ).…”
Section: Resultssupporting
confidence: 86%
“…These results are in agreement with earlier studies. Sharma, Prasad, and Chahar (), Bhattacharya, Srivastav, and Mishra (), and Kesbi et al () reported that the combined microwave‐convective drying method provided significant reductions in drying time for garlic, mushroom, and lemon samples. In addition, the drying time at 90 W–75 °C was shortened by 48.28% compared with the drying process realized at 90 W–55 °C.…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of the best model for portraying the drying curve of pestils, seven thin layer mathematical models were utilized. Models name and references were given, respectively, as; Page MR = exp(− kt n ) (Liu et al, ), Modified Page MR = exp [(− kt ) n ] (Toğrul, ), Logarithmic MR = a exp(− kt ) + c (Bhattacharya, Srivastav, & Mishra, ), Lewis MR = exp(− kt ) (Doymaz, ), Henderson and Pabis MR = a exp(− kt ) (Evin, ), Two‐Term Exponential MR = a exp(− kt )+(1 − a ) exp(− kat ) (Ertekin & Yaldiz, ), Wang and Singh MR = 1 + at + bt 2 (Wang & Singh, ).…”
Section: Methodsmentioning
confidence: 99%